Entrepreneurship networks in the literature from 2019 to 2022 - Cruz García Lirios; Gilberto Bermúdez Ruíz (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
The discussion of what devices and their dispositions are for an Internet user is the objective of this documentary work with a selection of sources indexed to international repositories; Dialnet, Latindex , Publindex , Redalyc and Scielo, considering the search by keywords; technology, Internet and networks (Facebook, WhatsApp, YouTube, Instagram, SnapChat , Periscope, Twitter). The discussion focused on the differences between habitus and intensive use, although the design of the review limits the scope and proposals of the work to the scenario of privacy and addiction among Internet users.